The relationship of problematic internet use with dissociation among South Korean internet users. (30th July 2016) - Lee, Tae Kyung; Roh, Sungwon; Han, Joo Hyun; Park, Se Jin; Soh, Min A; Han, Doug Hyun; Shaffer, Howard J
Abstract: This study examined patterns of problematic internet use (PIU) among South Korean internet users to investigate the association between PIU and dissociative experiences. Five hundred and eight participants between 20 and 49 years old were recruited through an online panel survey. Using logistic regression analysis with PIU as the dependent variable, we observed that the participants with PIU were more likely to have alcohol-related behaviors or problems, higher levels of perceived stress, and dissociative experiences. Participants' scores on the Korean version of the Dissociative Experiences Scale were positively correlated with the severity of PIU. Individuals with PIU and dissociation had more severe PIU and more severe mental-health problems than those with PIU but without dissociation. These findings suggest that treatment programs for persons with PIU should focus on helping them tolerate negative affect and increase their level of awareness to prevent the occurrence of dissociative experiences. Highlights: The association of problematic internet use (PIU) and dissociation was examined. Dissociation was positively correlated with the severity of PIU. Individuals with PIU and dissociation exhibited more severe mental health problems. Treatment programs for PIU should focus on increasing tolerance of negative affect. Increased self-awareness may help prevent the occurrence of dissociative states.